Biocatalytic Strategy for the Highly Stereoselective Synthesis of CHF2‐Containing Trisubstituted Cyclopropanes. (17th February 2021) - Carminati, Daniela M.; Decaens, Jonathan; Couve‐Bonnaire, Samuel; Jubault, Philippe; Fasan, Rudi
Abstract: The difluoromethyl (CHF2 ) group has attracted significant attention in drug discovery and development efforts, owing to its ability to serve as fluorinated bioisostere of methyl, hydroxyl, and thiol groups. Herein, we report an efficient biocatalytic method for the highly diastereo‐ and enantioselective synthesis of CHF2 ‐containing trisubstituted cyclopropanes. Using engineered myoglobin catalysts, a broad range of α‐difluoromethyl alkenes are cyclopropanated in the presence of ethyl diazoacetate to give CHF2 ‐containing cyclopropanes in high yield (up to >99 %, up to 3000 TON) and with excellent stereoselectivity (up to >99 % de and ee ). Enantiodivergent selectivity and extension of the method to the stereoselective cyclopropanation of mono‐ and trifluoromethylated olefins was also achieved. This methodology represents a powerful strategy for the stereoselective synthesis of high‐value fluorinated building blocks for medicinal chemistry, as exemplified by the formal total synthesis of a CHF2 isostere of a TRPV1 inhibitor. Abstract : CHieF2 cyclopropanes: A biocatalytic method was developed for the highly diastereo‐ and enantioselective synthesis of CHF2 ‐substituted cyclopropanes via myoglobin‐catalyzed carbene transfer. These biocatalysts offer broad substrate scope, enantiodivergent selectivity and could be applied to produce a difluoromethyl bioisostere of a drug candidate.